Research on the protection of athletes from injury by flexible conjugated materials in sports events - Liu, Jian; Ren, Tingting (Frontiers in Chemistry, 2023)
Sports are essential to everyone’s health because they assist athletes to establish physical and mental balance by strengthening muscles and ligaments. High-intensity training and low-quality equipment for sports tend to cause a wide range of injuries to the athlete. Higher education graduates’ regular education and lives are disrupted, either directly or indirectly, by sports injuries. Therefore, understanding the prevalence and root causes of college athletes’ injuries is crucial for enhancing student athletes’ performance and fostering healthy development. The ever-changing nature of injuries associated with sports and the patchy availability of rehabilitation facilities across India cause alarm. Inaccurately identifying players’ physical indications, uncomfortable clothing, and dissatisfaction with sports equipment are among the issues that can arise. The study investigates the potential of nanoparticles combined with sports flexible conjugate materials for injury prevention in athletes. The article proposed nanotechnology combined with flexible conjugated materials in sports events (Nano-FCM-SE) in sports training, explores the possibility of conjugated materials in enhancing the training effects of athletes, monitoring the status of sports, and bettering equipment. Sports equipment can help keep athletes safe by incorporating nanotechnology and flexible conjugated materials with superior optical, electrical, and other capabilities. Convenience, waterproof materials, flexibility, lightweight, aesthetics, breathability, and durability are evaluated for use in Nano-conjugated sports equipment materials. Evidence suggests that using flexible conjugated materials in athletic training can improve athlete performance and help the overall development of sports. The proposed method yields less negative results than MSI-TENG, TCM-MS, and RANSAC. The proposed damage severity model performs poorly relative to competitors (0.2). Compared to conventional models, the given models are effective on equipment. The sports injury protection system reported in this research has 5.17 percentage points greater detection efficiency than the current state of the art. Hierarchical strategies have the best RMSE for athlete safety. The findings of such methodologies in athlete safety on Nano conjugate materials and sports biology on sporting events and equipment underline the importance of precise data for athlete safety and performance.